Emission trading scheme, technological innovation, and competitiveness: Evidence from China's thermal power enterprises. (15th October 2022) - Wei, Yigang; Zhu, Rongqi; Tan, Longyan
Abstract: As flagship climate policy instruments, emission trading schemes (ETSs) are spreading, accelerating and strengthening globally. This study aims to explore whether the Porter hypothesis is present in China's ETS. Using the most recent data from 351 thermal power enterprises, the proposed agent-based model (ABM) creates a virtual decision-making and trading mechanism to identify ETS policy effects on enterprise technological innovation and competitiveness. Numerous findings and managerial insights emerge from the results. First, the weak Porter hypothesis cannot be realized in the early stages of China's ETS. However, when carbon price rises to 50–60 yuan/ton, the ETS spurs significant technological innovation. More importantly, the ETS-induced innovation effect is not associated with penalties or subsidies but is driven by allowance allocation and carbon price. Second, enterprise economic performance exhibits an inverted U-shaped trend. Specifically, innovation offsets may enhance enterprises' initial economic performance, while further tightening the allowance may have the opposite effect on competitiveness. Third, enterprise heterogeneity results in polarization, and the group of enterprises that proactively embrace technological innovation earn a higher profit. This work disentangles the dynamic effects of the weak and strong Porter hypotheses and provides empirical references for optimizing ETS design. Highlights: The dynamic effects of ETS on low-carbon technological innovation and competitiveness is analysed. A certain price of carbon (50–60 yuan) can significantly spur technological innovation. Enterprise economic performance exhibits an inverted "U-shaped" trend. Enterprise heterogeneity results in polarization of profits. This study test the "weak Porter hypothesis" and "strong Porter hypothesis" in the context of the ETS.